THE MAIN DEVELOPMENT VECTORS OF GEORGIAN NATIONALISM IN THE CONTEXT OF POLITICAL INSTABILITY Between the Traditions of the Political Nation and the Challenges of Radicalization - KIRCHANOV, Maxim (CENTRAL ASIA AND THE CAUCASUS, 2010)
Georgian nationalism is one of the main factors defining the formation of the political expanse in Georgia. Studies on national relations and the history of the autonomous formations in Abkhazia and South Ossetia have acquired particular relevance in the development of Georgian nationalism. Contemporary Georgian nationalists negatively assess the fact that Georgia was part of the Soviet Union: “Georgia was a country enslaved by Russia and Georgians lived in the Russian state, themselves becoming victims of the crimes of that state.”1 Contemporary nationalist-minded historians in Georgia believe that at the beginning of the 1920s, the country was forcibly annexed to the Soviet Union, and Moscow’s policy in Georgia did not meet the interests of the Georgian people. For example, Levon Toidze shows that “after the forced Sovietization of Georgia (February-March 1921), two equal (sic!) Soviet socialist republics of Georgia and Abkhazia were formed in its territory. This political and legal nonsense was the result of the negligent attitude toward Georgia’s national interests.”2Levon Toidze bases his analysis of Soviet national policy in Georgia on the firm belief that the Soviet model of resolving and settling national problems dramatically differed from the strategy by which the leaders of the Georgian Democratic Republic (which was eliminated after annexation to the Soviet Union) were guided. So, he emphasizes that “the idea of independence was supported and highly popular among the non-Russian nationalities, including the Caucasian. Georgia brought this idea to fruition in May 1918 by restoring its independence. Restoration of national statehood and the formation of the Georgian Democratic Republic were extremely important and joyous events in the history of the nation. Prominent officials of Abkhazia also genuinely shared the joy of the Georgian people at that time. We know that the Act of Independence of 26 May, 1918 was also signed by upstanding Abkhazians Varlam Shervashidze and Arzakan Emukhvari.”3Levon Toidze believes that whereas as part of Georgia the Abkhazians and Ossetians had the opportunity to develop and preserve their national cultures, languages, and traditions, Sovietization of these regions inevitably turned into Russification. In this respect, he stresses: “As for the question of Abkhazia joining the R.S.F.S.R., it can be evaluated as the logical result of the seditious policy conducted by certain political, clerical, and other forces, first of czarist and then of Soviet Russia, to alienate Abkhazia from Georgia, eliminate the Georgian language and Georgian culture from Abkhazia, and introduce the Russian language and Russian culture into the Abkhazian milieu (which was achieved).”4This shows a certain politicization of historical knowledge in present-day Georgia. History is used as a tool not only for political mobilization, but also in disputes with neighboring states with which Georgia has territorial conflicts. It is also worth noting that the arguments of Georgian historians in this context are politicized. Georgian nationalist authors are guided by political values and the ideas of the greater Georgian political and civilian nation, and not by ethnic myths, which is largely characteristic of their ideological opponents, the nationalist historians of Abkhazia and South Ossetia.